Postpartum depression and life experiences of mothers with an immigrant background living in the south of Sweden - Maude Johansson; Kajsa Ledung Higgins; Leoine Dapi Nzefa; Ylva Benderix (International Journal of Qualitative Studies on Health & Well-Being, 2023)
Purpose Postpartum Depression (PPD) —a common health problem for mothers’ postpartum increases the risk of negative interaction between mothers and infants as it reduces the former’s ability to respond to the latter’s needs appropriately. Migrant mothers exhibit a higher prevalence of risk factors for PPD. Hence, this study aimed to investigate migrant mothers’ life experiences pertaining to motherhood and PPD. Methods Qualitative interviews were conducted with 10 immigrant mothers in the south of Sweden during 2021. Results The qualitative content analysis revealed the following main themes: 1) PPD (two sub themes—psychosomatic symptoms and burden of responsibility due to feelings of loneliness); 2) mistrust of social services (one sub-theme—afraid of losing their children and Swedish social services’ lack of understanding); 3) inadequate healthcare (two sub-themes—limited healthcare literacy for migrant mothers and language barrier; 4) women’s coping strategy for well-being (two sub-themes—better awareness and understanding of the Swedish system and society, and freedom and independence in the new country). Conclusions PPD, mistrust of social services, and inadequate healthcare lacking personal continuity were common among immigrant women, thus precipitating discrimination—including lack of access to services because of limited health literacy, cultural differences, language barriers, and insufficient support.